POLITENESS STRATEGIES IN THE SOCIOLINGUISTIC PERSPECTIVEBASED ON RONALD WARDHAUGH'S "AN INTRODUCTION TO SOCIOLINGUISTICS" - Muhammad Riyan Habibi; Mufida Illah Ilmiah (INJOSEDU: International Journal of Social and Education, 2025)
Politeness is a crucial element in human communication, used to maintain interpersonal relationships and prevent conflicts. In sociolinguistics, politeness is studied as a linguistic strategy involving efforts to mitigate threats to the interlocutor's self-image, known as the concept of "face." This article explores politeness strategies as described by Ronald Wardhaugh in An Introduction to Sociolinguistics. Reviewing four main strategies—bald-on- record, positive politeness, negative politeness, and off-record—the article also discusses the significance of politeness in cultural contexts and its implications for cross-cultural communication research and practice. A deep understanding of politeness not only provides theoretical insights but also enhances communication effectiveness in various multicultural settings.